(untitled) (Bangladesh Journal of Child Health, 2020)
Bronchiolitis obliterans (BO) is a rare form of chronic obstructive lung disease that follows an insult to the lower respiratory tract characterized by inflammation and fibrosis of the terminal and respiratory bronchioles that lead to narrowing and/or complete obliteration of the airway lumen. Despite diverse etiology, similarity of pathological findings would suggest that BO is the final common pathway of response to different injuries to the lower respiratory tract. The characteristic symptom-complex includes dyspnea, chronic cough, sputum production and wheezing. Although histopathology remains the gold standard for diagnosis, high resolution computed tomographic scan is almost conclusive and replaces the invasive procedure in children. We report a case of BO in a seventeen months old child occurring after an episode lower respiratory tract infection requiring prolonged ventilation and subsequent development of subcutaneous emphysema, pneumomediastinum, hypertension and transient immunosuppression as complications. Our patient had a protracted clinical course with good response to corticosteroids, azithromycin and hydroxychloroquine. Bangladesh J Child Health 2020; VOL 44 (1) :55-59